The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physreva.84.033802
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-type solutions for multipole interface solitons in thermal nonlinear media

Abstract: We address the existence of multipole interface solitons in one-dimensional thermal nonlinear media with a step in the linear refractive index at the sample center. It is found that there exist two types of solutions for tripole and quadrupole interface solitons. The two types of interface solitons have different profiles, beam widths, mass centers, and stability regions. For a given propagation constant, only one type of interface soliton is proved to be stable, while the other type can also survive over a lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[9] In 2006, the interaction of nonlocal solitons in NLCMs can be controlled by the degree of nonlocality, which has been proved experimentally by Hu et al [23] In 2011, Ma et al addressed the existence of multipole interface solitons in one-dimensional thermal nonlinear media and found that there exist two kinds of tripole and quadrupole interface solitons and three types of fifth-order interface solitons, respectively. [24] They obtained the analytical solutions of surface solitons and breathers in an HNNM, and obtained the critical power and the period of breathers by numerical simulation. [25] In 2016, Alberucci et al discussed the deviation process of soliton and breather in real materials based on the Snyder-Mitchell model.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In 2006, the interaction of nonlocal solitons in NLCMs can be controlled by the degree of nonlocality, which has been proved experimentally by Hu et al [23] In 2011, Ma et al addressed the existence of multipole interface solitons in one-dimensional thermal nonlinear media and found that there exist two kinds of tripole and quadrupole interface solitons and three types of fifth-order interface solitons, respectively. [24] They obtained the analytical solutions of surface solitons and breathers in an HNNM, and obtained the critical power and the period of breathers by numerical simulation. [25] In 2016, Alberucci et al discussed the deviation process of soliton and breather in real materials based on the Snyder-Mitchell model.…”
Section: Introductionmentioning
confidence: 99%
“…It is note that interface solitons in such media are asymmetric because of the difference of the linear refractive index. For tripole and quadrupole interface solitons, there exist two different types of solutions under some special conditions [37].…”
Section: Introductionmentioning
confidence: 99%